First Confirmed Record of Platygomphus dolabratus Selys, 1854 (Odonata, Anisoptera) in Bangladesh - Shome, Ashikur Rahman; Alam, Md Mahabub; Roy, Ripon Chandra; Sultana, Shanjida; Rabbe, Md Fazle; Naser, M Niamul; Islam, Md Mazaharul; Biswas, Dipto; Jaman, Mohammad Firoj (Bangladesh Journal of Zoology, 2022)
Abstract not available Bangladesh J. Zool. 50 (1): 135-139, 2022